Robust data needed for island food systems research - Brewer, Tom; Roscher, Matthew; Eriksson, Hampus (WorldFish, 2024)
In this brief we present some preliminary analysis comparing food trade data sources focused on Pacific countries. The aim is to determine whether systematic analysis of various databases is warranted to identify the usefulness of each for various applications, such as analysis of commodities aggregated to the global region or specific national-level policy decisions. The context is the Pacific food system, so food data is the focus. Specifically, we compare trends of the BACI and PFTD databases across different aggregations of countries within the region to identify scales at which differences in database estimates are most pronounced.